The credibility of television in disseminating agricultural information to farmers in Malaysia - Hassan, Md. Salleh; Mohamed Shaffril, Hayrol Azril; Abu Samah, Bahaman; Ali, Muhamad Shamshahkat; Ramli, Nor Sabila; Azarian, Zoheir Sabaghpour (Canadian Center of Science and Education, 2012)
Agriculture and television are two different things that can be combined in many ways. Television has been utilized to further intensify agricultural development in Malaysia. This study attempts to discover the credibility of television when disseminating agricultural information to Malaysian farmers. A total of 400 farmers from four states in Malaysia were chosen as the respondents in this study. It was found that farmers view television as a credible source for disseminating clear and understandable agricultural information. In addition, it was considered credible due to its ability to provide up-to-date, unbiased and factual agricultural information. However, television is seen as less credible in terms of providing information at the right time, and is unable to provide all the necessary information.